2021
DOI: 10.4103/2452-2473.329627
|View full text |Cite
|
Sign up to set email alerts
|

Splenic infarction and pulmonary embolism as a rare manifestation of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) disease leads to a hypercoagulable state and associated with thrombotic events that can cause mortality and morbidity. Thrombotic events include both venous and arterial thrombosis. In this case report, we present a 68-year-old COVID-19 patient with multisystemic infarction who was admitted to the hospital by splenic infarction and later pulmonary embolism diagnosed during the stay in hospital despite anticoagulant use. It is important for emergency physicians to know that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…We also conducted a literature search across the Medline, PubMed, and Google Scholar databases regarding splenic artery infarct or occlusion in COVID-19 patients and found that such an infarct due to thrombosis appears seldom, with only 45 cases reported so far. Of these cases, 30 were male patients and 12 were female, while the patient's gender was not mentioned for three cases ( Table 2 ) [ 2 14 , 16 , 19 32 , 34 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also conducted a literature search across the Medline, PubMed, and Google Scholar databases regarding splenic artery infarct or occlusion in COVID-19 patients and found that such an infarct due to thrombosis appears seldom, with only 45 cases reported so far. Of these cases, 30 were male patients and 12 were female, while the patient's gender was not mentioned for three cases ( Table 2 ) [ 2 14 , 16 , 19 32 , 34 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increase in D-dimer levels is not sufficient to diagnose arterial or venous thrombosis owing to the considerable inflammatory reaction and significant rise in D-dimer levels following COVID-19 infection [ 2 , 16 ]. Nevertheless, the chances of hypercoagulability that accompanies this disease should raise suspicion of thrombotic events in unusual sites, and treatment with anticoagulants should start immediately after diagnosis [ 14 , 24 ]. A combination of more than two agents is sometimes necessary, and prolonged treatment, even after improvement, is, at times, inevitable [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection Cytomegalovirus [6][7][8] Epstein-Barr virus [9][10][11][12][13][14][15] Infective endocarditis [16][17][18][19][20][21][22] COVID-19 [23][24][25][26][27][28][29][30][31][32][33][34][35] Dengue virus [36] Mycoplasma pneumoniae [37,38] Malaria [39,40] Scrub typhus [41,42] Aspergillus pericarditis [43] Babesiosis [44] Malignancy including neoplasm and myeloproliferative diseases…”
Section: Causes Of Splenic Infarction Referencesmentioning
confidence: 99%